دور جدید میں مسلم مہاجرین کی آبادکاری سیرۃ النبی صلی اللہ علیہ و سلم کی روشنی میں : Modern age colonization of Muslim immigrant sin the light of Sirat al Nabi (SAW) - غلام یوسف (Seerat Studies, 2024)
The problem of Muslim refugee in the world a live challenge for modern world, because its have some causes thought of domination of Jews and rolling all over the world. Secondly over lights past and rolling on 3 continents Asia, Europe and Africa on the base of equality without help of non-Muslim. Non-Muslim dislike that things. Now they make planning to control the Muslim world and show that the defend Jihad a terrorism. In this way according to Jews and Hindus every Muslim is a tsarist because he is acting Jihad religiously and spread terrorism in land. Attack the Jew on Muslim country also a cause of creates problems for Muslim people to migration for other country to safety . In Islamic history when the Holy prophet (SAW) establish the first Islamic state at Medina, issues of immigrants were common that time, but he settled them with great planning .As a result it is a practically role model for mankind specially for Muslim country in modern age because Islam provides us a complete code of life and guide safety and welfare human in emergency and normal position without difference between Muslim and non-Muslim